Tafsir Tematik Islam Moderat Perspektif Al-Quran - Abdul Fattah (MAGHZA, 2020)
The study of the "Thematic Tafseer of Moderation Islam Quranic Perspective" explains the verses of the Qur'an about the moderation of Islam. The term can be relied upon against moderate word is the Wasathan, which in the Qur'an has mentioned the word wasath and it’s derivation as five times in the variation form, in surat al-Adiyat (100): 5, al-Baqarah (2): 143 al-Maidah (5): 89, al-Qalam (68): 28 and al-Baqarah (2): 238. This article is the literature study of thematic Tafseer by using the theory that is formulated by Abd al-Hayyi al-Farmawy. From the results of data mining and analysis, the authors conclude that moderate Islam in the Qur'an entered in three ways, namely moderation in aqidah, moderate in Sharia, and moderate in behaving.